2016
DOI: 10.1016/j.polymer.2016.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of porcine gastric mucin with various polycations and its influence on the boundary lubrication properties

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 42 publications
4
22
0
Order By: Relevance
“…The negative charge of mucin at neutral and alkaline pH is due to the presence of sialic acids (pKa = 2.6) located on the ends of the chains of a polysaccharide backbone [ 11 ]. Mucins from various sources have been employed to assemble multilayers using the following polycations: polyallylamine hydrochloride, poly-L-lysine, polyethylenimine, methylcellulose, chitosan, and lactoperoxidases (Mw 78 kDa, pI 8.3) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. The thickness of the formed multilayers depends on pH and ionic strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative charge of mucin at neutral and alkaline pH is due to the presence of sialic acids (pKa = 2.6) located on the ends of the chains of a polysaccharide backbone [ 11 ]. Mucins from various sources have been employed to assemble multilayers using the following polycations: polyallylamine hydrochloride, poly-L-lysine, polyethylenimine, methylcellulose, chitosan, and lactoperoxidases (Mw 78 kDa, pI 8.3) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. The thickness of the formed multilayers depends on pH and ionic strength.…”
Section: Introductionmentioning
confidence: 99%
“…This work aims at the development of new approaches for BAC microencapsulation based on the vaterite CaCO 3 crystals and mucin. Here the mucin from the porcine stomach has been used for the naturally-derived mucin widely employed for research [ 11 , 25 ]. The porcine gastric mucin has been shown to be structurally related to human gastric mucin [ 32 ] and is, therefore, a decent substitute of human gastric mucin because of its high availability and reduced number of ethical issues required for the research.…”
Section: Introductionmentioning
confidence: 99%
“…Both PAH and PDMAEMA are synthesized via radical polymerization techniques (e.g., vinyl addition, free radical, or controlled radical polymerization), employing the commercially available allyl amine and 2‐(dimethylamino)ethyl methacrylate monomers, respectively. Akin to chitosan, these synthetic materials were found to exhibit enhanced mucoadhesive properties in acidic environments owing to protonation of the amine derivatives . Furthermore these materials can be easily formulated into nanogels, liposomes, and films; however, in the case of PAH, toxicity issues have restricted its application somewhat .…”
Section: First Generation (Non‐specific) Primary Bonding Mucoadhesivementioning
confidence: 99%
“…ratio 50:9 of PGM:PAA as in "biosimilar" mucus, 7 except that BSA and lipids were excluded), and they were denoted as PGM:b-PEI and PGM:PAA, respectively. The mixing ratios for the two PGM:polyelectrolyte mixtures were determined based on the optimization in previous studies for PGM:b-PEI 21,22 and PGM:PAA, 7 respectively. Neat (unmixed) PGM and b-PEI (100 mg/mL) solutions were also employed for comparison, and denoted as PGM or b-PEI, respectively.…”
Section: A Mucin Polymers and Model Mucusmentioning
confidence: 99%
“…[17][18][19][20] In addition, recent studies on the interaction between PGM and b-PEI have also shown associative interaction mainly via electrostatic attraction and improved lubricating properties in the dilute concentration regime (≤ 1 mg/mL in total concentration). 21,22 An illustration of the chemical structure of PAA and b-PEI, as well as the interaction mechanism with PGM, is presented in It is hypothesized that the associative interaction between PGM and the two polyelectrolytes may be extended to the high concentration regime (ca. 50 -100 mg/mL in concentration).…”
mentioning
confidence: 99%